New Functional Tools for Antithrombogenic Activity Assessment of Live Surface Glycocalyx. Issue 9 (September 2016) - Dimitrievska, Sashka; Gui, Liqiong; Weyers, Amanda; Lin, Tylee; Cai, Chao; Wu, Wei; Tuggle, Charles T.; Sundaram, Sumati; Balestrini, Jenna L.; Slattery, David; Tchouta, Lise; Kyriakides, Themis R.; et al.
Abstract : Objective—: It is widely accepted that the presence of a glycosaminoglycan-rich glycocalyx is essential for endothelialized vasculature health; in fact, a damaged or impaired glycocalyx has been demonstrated in many vascular diseases. Currently, there are no methods that characterize glycocalyx functionality, thus limiting investigators' ability to assess the role of the glycocalyx in vascular health. Approach and Results—: We have developed novel, easy-to-use, in vitro assays that directly quantify live endothelialized surface's functional heparin weights and their anticoagulant capacity to inactivate Factor Xa and thrombin. Using our assays, we characterized 2 commonly used vascular models: native rat aorta and cultured human umbilical vein endothelial cell monolayer. We determined heparin contents to be ≈10 000 ng/cm 2 on the native aorta and ≈10-fold lower on cultured human umbilical vein endothelial cells. Interestingly, human umbilical vein endothelial cells demonstrated a 5-fold lower anticoagulation capacity in inactivating both Factor Xa and thrombin relative to native aortas. We verified the validity and accuracy of the novel assays developed in this work using liquid chromatography–mass spectrometry analysis. Conclusions—: Our assays are of high relevance in the vascular community because they can be used to establish the antithrombogenic capacity of many different types of surfaces such as vascular grafts and transplants. This work will also advance the capacity for glycocalyx-targeting therapeutics development to treat damaged vasculatures. Abstract : Supplemental Digital Content is available in the text.